Legal Analysis of Passive Euthanasia under Indonesian Health Law - K.Lubis; L.Harahap (International Medical Journal Corp. Ltd, 2025)
Introduction: Passive euthanasia, which involves withholding or withdrawing life-prolonging medical treatments, remains a highly controversial issue within the Indonesian legal landscape. While the medical community increasingly confronts situations where life support seems futile, the legal framework often appears ambiguous or overly restrictive. Methods: This research employs a normative juridical legal method, analyzing statutory provisions, judicial precedents, and doctrinal theories to evaluate the current legal status of passive euthanasia in Indonesia. Results: The study reveals a significant legislative gap between traditional criminal prohibitions and the evolving realities of modern medical practice. While the Indonesian Criminal Code strictly penalizes active forms of life-terminating acts, contemporary health regulations provide fragmented acknowledgments of the right to refuse treatment, leading to acute legal uncertainty for healthcare professionals. Discussion: The discussion synthesizes constitutional rights, medical ethics, and comparative law, highlighting that the lack of clear, standardized operational guidelines for passive euthanasia forces a reliance on judicial interpretation that may conflict with the patient's right to self-determination and the physician's duty of care. Conclusions: In conclusion, Indonesian health law requires comprehensive statutory refinement to explicitly regulate passive euthanasia, balancing human rights, cultural values, and medical necessities. The study recommends the immediate enactment of specific guidelines concerning advanced medical directives to provide clear legal protection for both patients and medical practitioners.